Stochastic stability and stabilization of discrete‐time singular Markovian jump systems with partially unknown transition probabilities. (24th February 2014) - Wang, Jianhua; Zhang, Qingling; Yan, Xing‐Gang; Zhai, Ding
Summary This paper considers the stochastic stability and stabilization of discrete‐time singular Markovian jump systems with partially unknown transition probabilities. Firstly, a set of necessary and sufficient conditions for the stochastic stability is proposed in terms of LMIs, then a set of sufficient conditions is proposed for the design of a state feedback controller to guarantee that the corresponding closed‐loop systems are regular, causal, and stochastically stable by employing the LMI technique. Finally, some examples are provided to demonstrate the effectiveness of the proposed approaches. Copyright © 2014 John Wiley & Sons, Ltd.